PENENTUAN PRIORITAS ATRIBUT PRODUSEN MINUMAN INSTAN DENGAN MENGGUNAKAN METODE ANALYTIC HIERARCHY PROCESS - RIOTISNA, I MADE AGUS; SUKARSA, I KOMANG GDE; SRINADI, I GUSTI AYU MADE; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika, 2023)
Decision Support System is a computer-based interactive system that helps decision making in utilizingnthe use of data and decision model models to solve problems that are semi-structured and unstructured The decision support system method is very diverse several methods that are often used, including the fuzzy logic method Expert System Method and the Analytical Hierarchy Process (AHP) method in this study will use the analytical hierarchy method  AHP Process to Determine the Priority of Instant Drink Manufacturer Attributes at PT Kembar Putra Makmur The results of the study showed that the highest criteria were found in the delivery criteria with a value of 0 27 and the highest alternative was found in alternative KINO producers with a value of 0 55